Wasiat Wajibah Sebagai Alternatif Pemberian Harta Peninggalan Kepada Ahli Waris Beda Agama - Deden Hidayat; Ali Nurdin; Fitriyani; Surahman (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
This article aims to review the obligatory will in relation to the distribution of inheritance/inheritance to heirs who are not legally entitled to a share of the inheritance due to different religions from the heir. Based on the facts in the community, or based on the possibility of legal phenomena that could occur in the community, giving inheritance to non-Muslims is sometimes unavoidable, especially if there are religious differences between family members. Not infrequently, because of the love of parents for their children or their families, parents as heirs still give shares to children or family members who have different beliefs, even though this is not justified in syara'. In Islamic law, there are known rules of changing laws that adapt to situations and conditions. These rules can be used to analyze various kinds of current conditions related to Islamic law, one of which is the matter of giving inheritance to non-Muslim children or family members. Using this rule perspective, giving a mandatory will to non-Muslims is possible as long as it contains benefits.